Flow cytometric analysis in Lagenaria siceraria (Cucurbitaceae) indicates correlation of genome size with usage types and growing elevation - ACHIGAN DAKO, ENOCH GBENATO; FUCHS, JOERG; AHANCHEDE, ADAM; BLATTNER, FRANCK R (My University, 2008)
The occurrence and extent of genome size variation within species is controversially discussed and thorough analyses are rare. Given the large morphological variation in Lagenaria siceraria (bottle gourds) and its wide distribution in Africa we here analysed (1) the genome size variation within cultivars of L. siceraria, (2) the correlation between genome size and morphological traits, and (3) the geographical patterns of DNA content within the species. We measured 2C-values of 366 individuals from 117 accessions of L. siceraria (2n=22) from Africa, America and Asia via flow cytometry with propidium iodide as DNA stain. We found that 2C-value in L. siceraria (0.683–0.776pg/2C) is about two times lower than previously reported and varies by about 12% among all accessions. Moreover, our results indicated a clear correlation of genome size with two different seed or usage types and with growing elevations in West Africa. Within the seed types genome size varies by 6.6 and 7.5%, respectively. The genome size differences in seed types of L. siceraria might indicate differences in their evolutionary history and necessitates a re-evaluation of the phylogenetic relationships within L. siceraria while the correlation between 2C-value and the elevation of the collecting sites might indicate an adaptation of genome size to an unknown ecological parameter connected to altitude. Flow cytometric analysis in Lagenaria siceraria (Cucurbitaceae) indicates... | Request PDF. Available from: https://www.researchgate.net/publication/225392729_Flow_cytometric_analysis_in_Lagenaria_siceraria_Cucurbitaceae_indicates_correlation_of_genome_size_with_usage_types_and_growing_elevation [accessed Mar 17 2018].